Economic crises as a motive for change in health care systems : a historical perspective with reference to the COVID-19 pandemic = Ekonomske krize kao poticaj promjena u zdravstvenom sustavu : povijesna perspektiva s osvrtom na pandemiju COVID-19 - Kaštelan, Snježana (Array, 2021)
Economic crises throughout history have often given an impetus for health and social reforms leading to the introduction of general healthcare systems and social equality in a large number of countries. The aim of this paper is to present the major economic crises and their effect on healthcare and social system chronologically. Bismarck’s and Beveridge’s model, the two most prominent healthcare models, which emerged primarily as a response to major economic crises, constitute the basis for the functioning of most health care systems in the world. An overview of historical events and experiences may be valuable in predicting future developments and potential effects of the crisis on healthcare systems and health in general. An analysis of past crises as well as current health and economic crisis caused by the COVID-19 pandemic and their impact on the healthcare system can facilitate the comprehension of the mechanisms of action and consequences of economic recession. It may also help identify guidelines and changes that might reduce the potential damage caused by future crises. The historical examples presented show that a crisis could trigger changes, which, in theiressence, are not necessarily negative. The response of society as a whole determines the direction of these changes, and it is up to society to transform the negative circumstances brought about by the recession into activities that contribute to general well-being and progress.